INOVASI PRODUK KEUANGAN SYARIAH DAN DAMPAKNYA TERHADAP STABILITAS EKONOMI - Dzakiyah Erlinda Agatha (Al-Iqtishad: Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the role of Islamic financial product innovation and its implications for macroeconomic stability within the framework of the Islamic economic system. Along with technological developments and the needs of the modern economy, various innovative Islamic financial products have emerged, such as sukuk variations, Islamic fintech, and Sharia-based digital banking services. This research uses a descriptive qualitative method through a literature study (library research) with a content analysis approach to recent relevant academic sources. The results show that Islamic financial product innovation significantly contributes to fund mobilization, efficient risk distribution, and strengthening of the financial intermediation structure. In addition, these innovations encourage the expansion of Islamic financial inclusion and serve as instruments to reduce speculative financial practices that negatively impact economic stability. Nevertheless, the effectiveness of these innovations is highly influenced by strict regulations, oversight, and compliance with Sharia principles. Therefore, strengthening Sharia compliance aspects becomes a crucial element in maintaining public trust and the overall resilience of the Islamic economic system.